An Update on State-of-the-Art Performance for Precision in Medical Laboratories - Jeremie M Gras; Delphine A Collin-Chavagnac; Florian Scherrer; Jean-Baptiste Raimbourg; Cyrille Biette; Michel Vaubourdolle; Anne J Vassault (The Journal of Applied Laboratory Medicine, 2026)
Abstract Background The European Federation of Clinical Chemistry and Laboratory Medicine (EFLM) has established a three-stage model of criteria to set analytical performance specifications (APS). The third model is based on state-of-the-art (SoA), which has been described as the highest level of analytical performance with currently available methods. However, an up-to-date, comprehensive, easily usable SoA database does not currently exist. Methods Data mining was performed using a data management package (Unity Real Time) for Internal quality control (IQC) and interlaboratory comparisons (ILC). For each analyte, the coefficient of variation (CV) values reported by the 50th, 90th, and 95th percentiles of laboratories were extracted and then the median intralaboratory CV50, CV90, and CV95 values were calculated. Results Using >775 million quality control (QC) measurements, an updated SoA database includes >100 analytes commonly performed in the fields of clinical biochemistry, hematology, hemostasis, therapeutic drug monitoring (TDM), and serology. The number of QC measurements of each analysis, for 3 specific levels of concentration, ranged from 1090 to 9 163 824 to evaluate the impact of concentration level on the method precision for each analysis. Conclusions This study provides an updated SoA database for precision that is of particular importance in circumstances where EFLM Biological Variation Database-derived APS do not exist, cannot be generated with current methods, or are inappropriate for pathophysiologic states. The impact of concentration level on precision data is also reported.